2008
DOI: 10.1128/jb.00541-08
|View full text |Cite
|
Sign up to set email alerts
|

The Vibrio cholerae Hybrid Sensor Kinase VieS Contributes to Motility and Biofilm Regulation by Altering the Cyclic Diguanylate Level

Abstract: Phosphorelay systems are important mediators of signal transduction during bacterial adaptation to new environments. Previously we described the vieSAB operon, encoding a putative three-protein component phosphorelay involved in regulating Vibrio cholerae virulence gene expression. At least part of the regulatory activity of VieSAB is exerted through the cyclic diguanylate (c-di-GMP)-degrading activity of the putative response regulator VieA. So far no direct evidence that VieSAB encodes a phosphorelay system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 42 publications
0
36
1
Order By: Relevance
“…Studies by Merrell et al (10) provided evidence that passage through the human host alters critical phenotypic properties that enhance the infectivity of V. cholerae in experimental animals. One of these is the down-regulation of motility/chemotaxis, which interestingly has been linked to the up-regulation of EPS production and thus biofilm formation (2,11,24). Our studies indicate that the host-induced changes in V. cholerae also include induction of in vivo biofilm communities that are especially efficient at CVEC formation and are therefore capable of long-term survival when introduced into aquatic environments.…”
Section: Discussionmentioning
confidence: 78%
“…Studies by Merrell et al (10) provided evidence that passage through the human host alters critical phenotypic properties that enhance the infectivity of V. cholerae in experimental animals. One of these is the down-regulation of motility/chemotaxis, which interestingly has been linked to the up-regulation of EPS production and thus biofilm formation (2,11,24). Our studies indicate that the host-induced changes in V. cholerae also include induction of in vivo biofilm communities that are especially efficient at CVEC formation and are therefore capable of long-term survival when introduced into aquatic environments.…”
Section: Discussionmentioning
confidence: 78%
“…By contrast, V. cholerae Cl strain O395, which is naturally HapR Ϫ , does not produce strong biofilms. In this V. cholerae Cl strain, deletion of the gene encoding the EAL protein VieA results in elevated vps expression and biofilm formation (50) The phosphodiesterase VieA is a component of the VieSAB signaling system that controls c-di-GMP levels and hence vps expression and biofilm formation in V. cholerae Cl (32,48,50). While VieA controls Ͼ100 genes in V. cholerae Cl , the role of VieA in V. cholerae El appears to be minor (1).…”
Section: Identification Of Ai-regulated Genes In V Cholerae Elmentioning
confidence: 99%
“…By contrast, V. cholerae Cl strain O395, which is naturally HapR Ϫ , uses the phosphodiesterase VieA, a component of the VieSAB system, to control c-di-GMP (Fig. 1B) (32,48,50). Recently, however, we showed that this V. cholerae Cl strain responds to CAI-1 and AI-2 to control the levels of a GGDEF protein through a HapR-independent pathway (15).…”
mentioning
confidence: 99%
“…In Pseudomonas aeruginosa, the mutation of either c-di-GMP phosphodiesterase gene, pvrR or rocR, also attenuated the virulence in a mouse infection model (7). In addition, c-di-GMP regulates bacterial pathogenesis through the control of motility or biofilm formation in P. aeruginosa, Yersinia pestis, V. cholerae, and S. Typhimurium (5,10,(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Another c-di-GMP phosphodiesterase that contains an HD-GYP domain breaks down c-di-GMP directly into two GMPs (4). c-di-GMP plays a role in the pathogenesis of many bacteria (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Vibrio cholerae vieA encodes a c-di-GMP phosphodiesterase, and deletion of this gene led to attenuation in an infant mouse model of cholera (13,14).…”
mentioning
confidence: 99%